Texte/image/manuscrit : une relation problématique ? - Elena Koroleva (Perspectives Médiévales)
This article examines the complex relations between image and text in the illuminated manuscripts of the Chronique dite de Baudouin d’Avesnes, dating from the 13th to the 15th century. In the first part I explore the practice of cutting out images in several manuscripts, which contributes to the emancipation of the miniature as an object. The loss of illuminations, resulting sometimes in the loss of whole folios, may hinder the recognition of a manuscript’s place within the tradition, as evidenced by the case of Arras, Bibliothèque municipale, 1043, largely ignored by scholars despite the fact that it preserves what is probably the original iconographic cycle of the chronicle. In the second part of the article I study the role of the first miniature, which is separate from the text and functions as an independent entity. The choice of subject for the first miniature – the creation of Eve in many copies of our text – is not directly linked to the content of the chronicle, but is instead prompted by the image itself and its iconography, which informs the reader of the serious character of the book and adds value to the manuscript as an object.